New iboga-type alkaloids from Ervatamia hainanensis. Issue 36 (23rd March 2016) - Liu, Zhi-Wen; Huang, Xiao-Jun; Xiao, Han-Lin; Liu, Guo; Zhang, Jian; Shi, Lei; Jiang, Ren-Wang; Zhang, Xiao-Qi; Ye, Wen-Cai
Abstract : The structures and absolute configurations of seven new iboga-type alkaloids1–7 were determined by spectroscopic data, Mosher's method, single crystal X-ray diffraction and ECD analyses. Abstract : Seven new iboga-type alkaloids (1–7 ) and six known ones (8–13 ) were obtained from Ervatamia hainanensis . Their structures with absolute configurations were determined by spectroscopic data, Mosher's method, single crystal X-ray diffraction and electric circular dichroism (ECD) analyses. The relationship between the absolute configuration of C-7 in iboga-type 7-hydroxyindolenine alkaloids and the Cotton effects in the ECD spectrum was established for the first time. The neural activities of these compounds were evaluated, and compound11 exhibited protective effects against MPP + (1-methyl-4-phenylpyridinium)-induced damage in primary cortical neurons.